The Post Office Scandal in the United Kingdom: Mental health and social experiences of wrongly convicted and wrongly accused individuals - Growns, Bethany (Legal and criminological psychology, 2024)
Background Wrongful criminal conviction can significantly impair the mental health of exonerees. However, much less is known about wrongful accusation: the impact of wrongful legal allegations or investigations—absent conviction—on mental health outcomes. Method To address this gap, we surveyed 101 victims of the Post Office Scandal in the United Kingdom who were wrongly accused, convicted and/or investigated for financial ‘losses’ that were actually caused by software errors. Results Most respondents reported clinically significant post-traumatic stress (67%) and depressive (60%) symptoms—irrespective of the outcome of their case. These results suggest that both wrongful accusation and wrongful conviction can significantly impair mental health. Conclusion Our findings have important implications for victims of the Post Office Scandal and highlight the unique needs of people impacted by flawed convictions and flawed legal accusations. Our findings underscore the need to provide exonerees with holistic postrelease support and demonstrate that this support should also be extended to victims of wrongful accusation.